Determinación de la presencia de Macracanthorhynchus hirudinaceus en cerdos que se despostan en el Camal Municipal de la Ciudad de Babahoyo - Beltrán Mayorga, Boris Omar (2014)
The present investigation work was carried out in the Municipal Slaughterhouse that is located in the city of Babahoyo, Province of Los Ríos whose geographical conditions are: 79º 32' 13 '' of longitude west and 1º 49' 20 '' 'of south latitude, to an altitude of 8 masl. The facilities of the Municipal Slaughterhouse are located in the citadel "The Pireo" of the urban parish Camilo Ponce and it possesses a faenamiento room with all the technical specifications and in good sanitary state. The climate in the canton is tropical humid, with a half temperature of 26 ºC, and humidity average of the 75 - 80%. For the evaluation of the experimental results the percentage method was used and the presence of Macracanthorhynchus hirudinaceus was determined this way in the pigs that were despostaron in the municipal slaughterhouse of the city of Babahoyo...........